2019
DOI: 10.1108/ijqrm-01-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

To what extent do quality procedures determine the performance of French SMEs?

Abstract: Purpose Although a considerable bulk of literature has focused on the relationship between the implementation of quality assurance certification and the corporate performance of companies, still few are the works devoted to small- and medium-sized enterprises (SMEs). The purpose of this paper is to provide additional evidence for the impact of implementing quality assurance and control certificates on the performance of French SMEs. Design/methodology/approach With a view to determining the effect of certifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…For example, Rojas-Lema et al (2020) point out that the research about performance measurement in SMEs on different business contexts is limited. Moreover, Bannour and Mtar (2019) support the view that SMEs strive to gain a foothold in markets across national borders, in a bid to remain profitable and increase their performance. Business models should be extended by studying specific capabilities which may contribute to competitive advantage for SMEs' international performance (Falahat et al , 2020).…”
Section: Introductionsupporting
confidence: 57%
“…For example, Rojas-Lema et al (2020) point out that the research about performance measurement in SMEs on different business contexts is limited. Moreover, Bannour and Mtar (2019) support the view that SMEs strive to gain a foothold in markets across national borders, in a bid to remain profitable and increase their performance. Business models should be extended by studying specific capabilities which may contribute to competitive advantage for SMEs' international performance (Falahat et al , 2020).…”
Section: Introductionsupporting
confidence: 57%
“…Quality performance (QP): The realisation of a global playing field in the creation and offering of goods and services has laid more emphasis on quality (Sethi and Sethi, 2009), even as customers emphasise quality for less cost (Bannour and Mtar, 2019). The relevance of QP is invaluable as it is tethered to the customer satisfaction performance and financial performance of all manufacturing firms (Goetsch and Davis, 2014;Tomic and Brkic, 2018).…”
Section: Impact Of Quality Managementmentioning
confidence: 99%
“…In the manufacturing sector, quality remains crucial amidst the growing desire for mass customisation and instantaneous doorstep delivery (Grover and Malhotra, 2003). Since consumers expect higher performance at lower prices yearly (Bannour and Mtar, 2019), firms employ quality management to reduce cost and improve quality simultaneously for customer satisfaction (Abbas, 2020). In fact, Stevenson (2012) opines that end users consider quality and price before any purchase, and without them a product is not competitive to them.…”
Section: Introductionmentioning
confidence: 99%
“…SMEs in developing countries strive to obtain a superior competitive advantage in the national market due to competition from international firms to remain profitable and increase their performance. Nevertheless, limited studies have identified the factors and variables that contribute to developing SMEs' performance in emerging economies (Bannour & Mtar, 2019;Rojas-Lema et al, 2020).…”
Section: Organizational Performancementioning
confidence: 99%